An Analysis of Event Experiences (A Case Study of The Script's Satellites World Tour at Jatim Expo, Surabaya) - Ni Putu Lilik Widyayanthi; Isvari Ayu Pitanatri; Ni Kadek Sri Mirayani; Putu Wira Parama Suta (Yayasan Literasi Sains Indonesia, 2025)
This study analyzes the event experience of The Script’s Satellites World Tour at Jatim Expo, Surabaya, focusing on four key dimensions: affective engagement, cognitive engagement, physical engagement, and experiencing newness. Using a case study design with a descriptive qualitative approach, data were gathered through surveys and semi-structured interviews with five concert attendees. The findings highlight that the concert successfully delivered a memorable audience experience across all four dimensions, providing both entertainment and reflective value. Nonetheless, some weaknesses were identified, especially regarding the placement of the festival area, which limited visibility and reduced the emotional connection for certain audience members. Despite these challenges, the event effectively engaged attendees affectively, cognitively, and physically, while offering them a sense of novelty and excitement. To further improve future audience experiences, it is recommended that concert organizers assess and enhance the technical setup and venue layout to ensure better visibility and stronger engagement for all attendees.